2014
DOI: 10.1111/aji.12284
|View full text |Cite
|
Sign up to set email alerts
|

Novel Morphological Findings of Human Sperm Removal by Leukocytes in In Vivo and In Vitro Conditions: Preliminary Study

Abstract: Our morphological data suggest that human germ cells activate leukocytes triggering both traditional phagocytosis and a novel trapping mechanism, followed by extensive sperm elimination.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
10
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 45 publications
5
10
1
Order By: Relevance
“…TEM as well as SEM analyses confirmed that both effector mechanisms are displayed by PMN exposed to vital spermatozoa, namely, phagocytosis and the NETosis process. We found both fine and coarse networks; some NETs merged when they were released by nearby PMN, and this may also establish a neutrocyte cooperation system for more effective sperm elimination as postulated elsewhere (17). The immunofluorescence images showed that the neutrophils establish multiple phagocyte centers of differing sizes to form cluster-like structures; they may occur on the head or the tail and prevent the spermatozoa from moving.…”
Section: Discussionsupporting
confidence: 70%
“…TEM as well as SEM analyses confirmed that both effector mechanisms are displayed by PMN exposed to vital spermatozoa, namely, phagocytosis and the NETosis process. We found both fine and coarse networks; some NETs merged when they were released by nearby PMN, and this may also establish a neutrocyte cooperation system for more effective sperm elimination as postulated elsewhere (17). The immunofluorescence images showed that the neutrophils establish multiple phagocyte centers of differing sizes to form cluster-like structures; they may occur on the head or the tail and prevent the spermatozoa from moving.…”
Section: Discussionsupporting
confidence: 70%
“…High incidences of P-fimbriated E. coli strains have been found in acute prostatitis [38]. Our experience with P-fimbriated E. coli serotype O75:HNT has confirmed direct contact adhesion to the surface of sperm midpiece, principal piece, and acrosome, mediated by projections and sperm agglutination, and resulting in ultrastructural alterations in regions with attached bacteria (Figure 1) [39]. It should be emphasized that despite the ultrastructural evidences observed in both in vitro and in vivo conditions, there is no general consensus on a negative relevance of the bacteriospermia on sperm morphology parameters, assessed as a part of the routine sperm analysis.…”
Section: Coli Staphylococcus (S) Aureus Enterococcus (E) Faecalissupporting
confidence: 52%
“…Most probably, the monitoring of a complex network of molecular, biochemical, immunological, oxidative, and inflammatory parameters in semen may offer a chance to better understand the mechanisms leading to subfertility and infertility caused or complicated by microbial infection of the semen. The value of such observations would be significant, [9,10,31,39,51]. (1) Bacteria and their toxins trigger the infiltration of immune cells connected with (2) the production and release of large amounts of ROS (neutrophils, macrophages) as well as (3) immune regulatory factors (from macrophages, lymphocytes, monocytes, and dendritic cells); the cytokines may modulate the activities of the prooxidative and antioxidative systems, which may also result in the enhanced secretion of ROS; (4) When the amounts of ROS exceed the potential of the antioxidative defence, oxidative stress occurs; (5) Oxidative stress induces lipid sperm membrane peroxidation and leads to a series of detrimental defects in the spermatozoa, including lipid asymmetry loss, motility loss, PS externalization, and loss of ∆Ψm.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations